Kemandirian Ekonomi Pesantren Ditinjau Dari Aset dan Operasionalnya - Singgih Muheramtohadi; Septiana Na'afi (Jurnal Ilmiah Ekonomi Islam, 2022)
Minister of Religious Affairs, Yaqut Chalil Qaumas in 16th of December 2021 Stated that he would release the Pesantren Economic Independence Program. Pesantren have make the breakthrough with maximilixing their economic potency. The model that will be purposed is the giving investment capital with associate to BUMN and make them as ‘foster parents’ for pesantren in developing its business. This program can’t be assessed how it will work. But the term of Independency Pesantren in Economy, must be explained in detail how the independency of pesantren so far. This write will explain two sides, they are the independency of its asset and independency of its operational. Is it true that the these institutions depend on other parties? The discussion in this write use description and analysis methods. And the result of this discussion are the pesantren have the culture power that take root in the middle of society. And the aid and grant that received from others, including alumni, not considered the aid from others, but those the potency of pesantren.